Physicochemical conditions of GaAs/GaAsxNy/GaN nanochips stability - N. V. Komarovskih; L. V. Fomina; S. A. Beznosyuk (Chimica Techno Acta)
In this work the study of the stability nanochips GaAs / GaAsxNy / GaN is presented. For the calculation of parameters used quantum-chemical and thermodynamic approaches. The calculations of the surface free energy nanochips within the models used show that a significant contribution to the crystalline structure stability of the GaN layer is the molar concentration of nitrogen atoms in the intermediate layer GaAsxNy nanochips GaAs / GaAsxNy / GaN.